SOCIOLOGICAL METHOD AND ITS APPLICATION IN LITERATURE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article provides an overview of the application of the sociological method in literature and art. However, it has been analyzed using examples and extensive insights have been provided through research.